Avaliação da atividade não citotóxica do veneno da cobra bothrops pauloensis em células mononucleares do sangue periférico humano - Castro, Fernanda de Oliveira Feitosa de (2011)
Snake s venoms are complexes mixtures of proteins and peptides, aminoacids, nucleotides, lipids and carbohydrates, that showes importants biologicals activities like cytotoxicity, neurotoxicity, systemic myolysis, cardiotoxicity, kidney damage, hematologic disorders, like others. These molecules has shown pharmacological potential components with potent action against bacterias, virus and fungis. This present work aimed assed no cytotoxic effect of the crude venom of the snake Bothrops pauloensis in the culture of peripheral blood mononuclear cells (PBMC). After standardization of obtaining PBMC and evaluation of ideal concentration of fitohemagglutinin (PHA) and interleukin-2 (IL-2) for the cell culture was performed the evaluation of no citotoxic effect on CMN by different doses of crude venom of Bothrops pauloensis. The CMN was separated by density gradient, posterior being cultured. The evaluation of the no cytotoxic activity of the venom was performer by the visualization of the plate after 24, 48 and 72 hours. The concentration 0,05 mg/ml did not appear citotoxic activity, suggesting the possibility of using in testing with CMN infected by viruses, bacteria and fungi.